Inhabiting implication in racial oppression and in relational psychoanalysis - Kabasakalian-McKay, Rachel, 1961-; Mark, David, 1955- (London ; New York, New York : Routledge, 2023)
"What does it feel like to encounter ourselves and one another as implicated subjects, both in our everyday lives and in the context of our work as clinicians, and how does this matter? With contributions from a diverse group of relational psychoanalytic thinkers, this book reads Michael Rothberg's concept of the implicated subject - the notion that we are continuously implicated in injustices even when not perpetrators - as calling us to elaborate what it feels like to inhabit such subjectivities in relation to others both similarly and differently situated. Implication and anti-Black racism are central to many chapters, with attention given to the unique vulnerability of racial minority immigrants, to Native American genocide, and to the implication of ordinary Israelis in the oppression of Palestinians. The book makes the case that the therapist's ongoing openness to learning of our own implication in enactments is central to a Relational sensibility and to a progressive psychoanalysis. As a contribution to the necessary and long-overdue conversation within the psychoanalytic field about racism, social injustice, and ways to move toward a just society, this book will be essential for all relational psychoanalysts and psychotherapists"--
Includes bibliographical references and index.
Description based on print version record.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2018. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Psychoanalysis and racism; Interpersonal psychotherapy; Electronic books